Leadership transfer in rural communities: A mixed methods investigation. Issue 3 (27th May 2021) - Hastings, Lindsay; Sunderman, Hannah; Hastings, Matthew; McElravy, LJ; Lusk, Melissa
ABSTRACT: The United States is poised to experience one of the largest transfers of leadership in its history, markedly impacting rural community sustainability efforts. The purpose of this exploratory sequential mixed methods study was to identify themes related to rural leadership transfer using grounded theory and to test the facilitation of effective leadership transfer using structural equation modeling. Adult and youth leaders (N = 19) from three nominated rural communities comprised the qualitative phase and secondary data from a 2015 rural survey (N = 1991) comprised the quantitative phase. Mixed methods results indicated the environment conducive for effective leadership transfer (via broadened civic engagement) was facilitated when community hope became contagious based upon community development efforts achieved by hopeful, persistent community leaders. The presented findings offer greater precision to leadership research in community contexts and enable increased effectiveness in facilitating community leadership transitions, thus enhancing their generative capabilities.